A novel hybrid approach for in-situ determining the thermal properties of subsurface layers around borehole heat exchanger. (November 2018) - Akhmetov, Bakytzhan; Georgiev, Aleksandar; Popov, Rumen; Turtayeva, Zarina; Kaltayev, Aidarkhan; Ding, Yulong
Graphical abstract: Highlights: A new hybrid approach is applied to estimate subsurface thermal properties. Temperature sensors along the BHE showed intensive heat losses at groundwater level. Subsurface thermal conductivity calculated by TRT was higher than the hybrid method. TRT results may not be accurate when a groundwater is present in the subsurface. The hybrid approach helps to evaluate depth dependent subsurface thermal properties. Abstract: Performance of shallow geothermal systems such as borehole thermal energy storage (BTES) and ground source heat pump (GSHP) mainly depends on the thermal properties of the subsurface and proper design of borehole heat exchangers (BHE). This paper introduces a novel hybrid approach for measuring the effectiveness of BHEs and surrounding subsurface thermal properties, which combines traditional thermal response test (TRT) with the borehole temperature relaxation method (BTR), based on two dimensional radial conductive heat transfer. The new method allows for: (1) evaluation of how convective heat loss at groundwater layers influence estimation of subsurface thermal properties; (2) examination of non-uniform heat transfer through a BHE to stratified subsurface layers; and, (3) calculation of depth-dependency of thermal properties of unsaturated subsurface layers. The hybrid approach was tested using a 50 m U-type BHE, the results of which indicated that convective heat transfer at the groundwater level altered the real value of effective thermal conductivity from 0.45 to 1.56 W/m K. The non-uniformity of heat transfer along the BHE was confirmed by calculations that showed subsurface thermal conductivities were depth dependent, varying between 0.34 and 0.61 W/m K.